Foreign exchange and its derivatives. - Tan, Cindy Tiam Hon. (2009)
The strong growth in the foreign exchange transactions has called for technological innovation and expertise in foreign exchange risk management and as such, new products such as derivatives and regional financial instruments are being looked at by banks and market makers. Exchanged traded futures markets in this instance, have been regarded as the most organized, liquid, flexible and low cost amongst all the derivatives for hedging purposes.